Targeting immunometabolism of neoplasms by interleukins: A promising immunotherapeutic strategy for cancer treatment. (10th October 2021) - Zhu, Ziwen; Parikh, Pooja; Zhao, Hongyun; Givens, Nathan T.; Beck, Damien B.; Willson, Conner M.; Bai, Qian; Wakefield, Mark R.; Fang, Yujiang
Abstract: In recent years, tumor metabolism has become a prevalent research topic for scientists and pharmaceutical companies. As research in the field has progressed, the metabolism-based therapy of tumors has ushered in new opportunities. Most tumors emerge and evolve under selective pressure from their microenvironment, which promotes the diversification of both neoplastic and non-neoplastic compartments of the tumor microenvironment (TME), and finally reaches a certain degree of intratumoral heterogeneity. As a result of the tumor intratumoral heterogeneity, tumor cells often possess a complex energy metabolism phenotype. During tumor progression, the metabolism for both tumor parenchyma and stroma is reprogrammed. The tumor stroma mainly consists of the extracellular matrix, fibroblasts, and immune cells. Interestingly, tumor-infiltrating immune cells utilize different metabolites based on their subtype and function, and these immunometabolic pathways can be modified in the TME. In particular, interleukins play a vital role in the activation and differentiation of immune cells and have exhibited multiple effects on tumor cell neoplasia, invasion, and metastasis. In this review, we summarize the common mechanisms of interleukins affecting the tumor and tumor-infiltrating immune cells metabolically and discuss how these mechanisms may lead to novel therapeutic opportunities. This review might contribute to the novel development of cancer immunotherapy. Highlights: Interleukins play a crucial role in cancer immunometabolism. Interleukins usually affect cancer cells directly and indirectly through immune cells. Most of Interleukins metabolism studies focused on glycolysis and lipid metabolism.